2008
DOI: 10.1007/s10526-008-9166-9
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent pseudomonad mixtures mediate disease resistance in rice plants against sheath rot (Sarocladium oryzae) disease

Abstract: Plant growth-promoting rhizobacterial (PGPR) strains were isolated from different agroecosystems of Tamil Nadu, India, and were tested for their efficacy against the sheath rot pathogen Sarocladium oryzae under in vitro, glasshouse and field conditions. Vigour and a relative performance index (RPI) were used to assay the growth promotion and antagonistic activity of Pseudomonas strains against S. oryzae under in vitro conditions. The results revealed the significant performance by strains Pf1, TDK1 and PY15 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 47 publications
3
39
0
Order By: Relevance
“…Isolates of P. fluorescens were also reported to be effective for reducing the population of root-knot nematode, Meloidogyne incognita in medicinal coleus (Seenivasan and Devrajan 2008) and potato cyst nematode, Globodera rostochiensis in potato (Seenivasan, Devrajan, and Selvaraj 2007). Since strains of P. fluorescens are capable of surviving in rice rhizosphere soil, inside the rice root and on the root surface (rhizoplane) under rice ecosystems (Vidhyasekaran et al 1997;Saravanakumar, Lavanya, Muthumeena, Raguchander, and Samiyappan 2009), the exploration of P fluorescens for the control of M. graminicola could be of practical significance. The objective of this study is to determine the bio-control efficacy of P. fluorescens strains PF1, TDK1 and PY15 singly and as mixture against M. graminicola under in vitro, glass house and field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Isolates of P. fluorescens were also reported to be effective for reducing the population of root-knot nematode, Meloidogyne incognita in medicinal coleus (Seenivasan and Devrajan 2008) and potato cyst nematode, Globodera rostochiensis in potato (Seenivasan, Devrajan, and Selvaraj 2007). Since strains of P. fluorescens are capable of surviving in rice rhizosphere soil, inside the rice root and on the root surface (rhizoplane) under rice ecosystems (Vidhyasekaran et al 1997;Saravanakumar, Lavanya, Muthumeena, Raguchander, and Samiyappan 2009), the exploration of P fluorescens for the control of M. graminicola could be of practical significance. The objective of this study is to determine the bio-control efficacy of P. fluorescens strains PF1, TDK1 and PY15 singly and as mixture against M. graminicola under in vitro, glass house and field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the Pseudomonas fluorescens and endophytic Bacillus subtilis have received particular attention throughout the global science because of their catabolic versatility, excellent root colonizing ability and their capacity to produce a wide range of enzymes and metabolites that favour the plant withstand under varied biotic and abiotic stress conditions (Ramamoorthy et al 2001;Vivekananthan et al 2004;Mayak et al 2004;Saravanakumar and Samiyappan 2007). Though there are several reports on the management of plant diseases (Wang et al 2000;Saravanakumar et al 2009) and pests (Saravanakumar et al 2007a) using PGPB, very little is known about the role of PGPB in mediating drought resistance in field crops. Therefore, the objective was fixed: (a) to evaluate the promising strains of P. fluorescens and B. subtilis to enhance drought resistance on green gram plants and (b) to study the differential enzymatic and protein activity during water stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of non-bacterized plants, only very few isoforms were expressed upon pathogens inoculation. Similarly, Saravanakumar et al (2009) reported enhanced induction of PO in rice plants treated with combination of Pseudomonas fluorescens stains Pf1 þ TDK1 þ PY15 upon challenge inoculation with sheath rot pathogen compared with untreated control plants. Activity was found to be greatest on the fifth day and after that it declined.…”
mentioning
confidence: 85%
“…These findings revealed that, in addition to disease control, endophytes also enhance the plant growth and yield. Saravanakumar et al (2009) reported that in addition to enhancing the induction of defence enzymes in rice plants, P. fluorescens strains Pf1 þ TDK1 þ PY15 increase the vigour index of rice seedlings. Karthiba et al (2009) also reported that PGPR consortium combining P. fluorescens strains (Pf1 and AH1) and Beauveria bassiana (isolate B2) effectively reduced the sheath blight disease in rice in addition to higher accumulation of defence enzymes, PO and PPO, against R. solani and significantly rice grain yield had increased than untreated control.…”
Section: Endophytic Bacteria and Rice Sheath Blightmentioning
confidence: 99%